2017
DOI: 10.1038/srep46489
|View full text |Cite
|
Sign up to set email alerts
|

Isothiocyanates induce UGT1A1 in humanized UGT1 mice in a CAR dependent fashion that is highly dependent upon oxidative stress

Abstract: Isothiocyanates, such as phenethyl isothiocyanate (PEITC), are formed following the consumption of cruciferous vegetables and generate reactive oxygen species (ROS) that lead to the induction of cytoprotective genes such as the UDP-glucuronosyltransferases (UGTs). The induction of ROS activates the Nrf2-Keap 1 pathway leading to the induction of genes through antioxidant response elements (AREs). UGT1A1, the sole enzyme responsible for the metabolism of bilirubin, can be induced following activation of Nrf2. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…In hUGT1 mice, oral administration of PEITC induced UGT1A1 expression in liver and small intestine, which led to a decrease in their serum bilirubin levels [91]. It was further demonstrated that the Cyp2b10 was also induced by the PEITC treatment in the liver and small intestine.…”
Section: Gene Induction By Isothiocyanates In Hugt1 Micementioning
confidence: 99%
“…In hUGT1 mice, oral administration of PEITC induced UGT1A1 expression in liver and small intestine, which led to a decrease in their serum bilirubin levels [91]. It was further demonstrated that the Cyp2b10 was also induced by the PEITC treatment in the liver and small intestine.…”
Section: Gene Induction By Isothiocyanates In Hugt1 Micementioning
confidence: 99%
“…Sugatani et al (2001) first characterized the phenobarbital (Pb) responsive enhancer module in the human UGT1A1 gene that binds to the constitutive active receptor (CAR). When hUGT1 neonatal mice are treated with Pb, liver UGT1A1 is induced and TSB levels are dramatically reduced (Chen et al, 2012;Shibuya et al, 2013;Yoda et al, 2017;Yueh et al, 2017). However, in hUGT1/Car 2/2 mice, Pb administration does not induce UGT1A1 and has no impact on neonatal TSB levels, confirming genetically that CAR regulates the UGT1A1 gene.…”
Section: Resultsmentioning
confidence: 72%
“…However, in hUGT1/Car 2/2 mice, Pb administration does not induce UGT1A1 and has no impact on neonatal TSB levels, confirming genetically that CAR regulates the UGT1A1 gene. In hUGT1 mice, the UGT1A1 gene can be transcriptionally induced by other XNRs, including the pregnane X receptor (PXR) (Chen et al, 2012), the peroxisome proliferator-activated receptor alpha (PPARa) (Senekeo-Effenberger et al, 2007), the liver X receptors alpha and beta (LXRa/b; unpublished observations), and the environmental sensors, the aryl hydrocarbon receptor (AhR) (Yueh et al, 2003;Chen et al, 2005;Bonzo et al, 2007), and Nrf2 (Yueh and Tukey, 2007;Yoda et al, 2017). The oral or intraperitoneal administration of ligands capable of activating these receptors in neonatal hUGT1 mice leads to the Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats fed a PEITC‐supplemented diet for two weeks, at the low dose corresponding to human dietary intake both quinone reductase and GST were elevated in the liver, and an increase in epoxide hydrolase activity was seen at higher doses; none of these activities was altered by the treatment in the lung, whereas in the kidney modest rises in quinone reductase and epoxide hydrolase occurred but only at higher doses, demonstrating tissue differences in the modulation of these enzymes by isothiocyanates . Oral administration of PEITC to humanized UGT 1 mice elevated UGT1A1 activity in the liver and intestine that led to a decrease in total serum bilirubin since this enzyme is responsible for the glucuronidation of bilirubin …”
Section: Modulation Of the Detoxification Of Chemical Carcinogens By mentioning
confidence: 97%